Novel Bis- and Mono-Pyrrolo[2,3-d]pyrimidine and Purine Derivatives: Synthesis, Computational Analysis and Antiproliferative Evaluation - Andrea Bistrović Popov; Robert Vianelo; Petra Grbčić; Mirela Sedić; Sandra Kraljević Pavelić; Krešimir Pavelić; Silvana Raić-Malić (Molecules, 2021)
Novel symmetrical bis-pyrrolo[2,3-d]pyrimidines and bis-purines and their monomers were synthesized and evaluated for their antiproliferative activity in human lung adenocarcinoma (A549), cervical carcinoma (HeLa), ductal pancreatic adenocarcinoma (CFPAC-1) and metastatic colorectal adenocarcinoma (SW620) cells. The use of ultrasound irradiation as alternative energy input in Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC) shortened the reaction time, increased the reaction efficiency and led to the formation of exclusively symmetric bis-heterocycles. DFT calculations showed that triazole formation is exceedingly exergonic and confirmed that the presence of Cu(I) ions is required to overcome high kinetic requirements and allow the reaction to proceed. The influence of various linkers and 6-substituted purine and regioisomeric 7-deazapurine on their cytostatic activity was revealed. Among all the evaluated compounds, the 4-chloropyrrolo[2,3-d]pyrimidine monomer 5f with 4,4′-bis(oxymethylene)biphenyl had the most pronounced, although not selective, growth-inhibitory effect on pancreatic adenocarcinoma (CFPAC-1) cells (IC50 = 0.79 µM). Annexin V assay results revealed that its strong growth inhibitory activity against CFPAC-1 cells could be associated with induction of apoptosis and primary necrosis. Further structural optimization of bis-chloropyrrolo[2,3-d]pyrimidine with aromatic linker is required to develop novel efficient and non-toxic agent against pancreatic cancer.